Biodiesel Production from a Mixture of Rubber Seed Oil and Waste Oil Through the Alcoholysis Process with Catalysts Based on Vegetable Waste - I Ibrahim; A M Syam; M Muhammad; Zainuddin Ginting; S Maliki (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
The increasing types of people needs along with the times have resulted in the need for energy increasing so that the supply of energy, especially energy that cannot be renewed (unrenewable energy) is decreasing. Currently, almost 80% of the world's energy needs are met by fossil fuels. In fact, the use of fossil fuels can cause global warming. To reduce dependence on fossil fuels as an energy source, it is necessary to search for energy sources that can be used as alternative fuels that are environmentally friendly. Indonesia is an agricultural country that is overgrown with plantation crops that produce various kinds of waste such as rubber seeds which contain oil. This plant produces a lot of wasted seeds that are not useful. Therefore, researchers want to research the oil from rubber seeds to be a biodiesel product and in order to get high quality results. This study regulates several independent variables, namely the alcoholysis temperatures: 650C, 700C and 750C and the alcohol volume: 200 ml, 250 ml and 300 ml. The process is carried out by extraction using the alkolysis method. The best yield yielded 60.5%, with the best yield of biodiesel from alcoholysis obtained at a volume of 250 ml of ethanol and a temperature of 75oC with a density of 09 kg/m3 and a viscosity of 3,285 mm2/s (cSt), fulfilling the requirements of SNI 7182:2015. Based on the results of GC analysis, the main fatty acid components in the sample were at peak 1, namely saturated fatty acids in the form of palmitic acid at 44,28% and peak 4, namely unsaturated fatty acids in the form of oleic acid at 31.99%.